Fair Value Measurement and Firm Performance of Quoted Manufacturing Companies in Nigeria - Joy Esosa Egbon–Aghaleleghian; David Jerry Oziegbe (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This study examined fair value measurement and firm performance of quoted manufacturing companies in Nigeria. The study used data from thirty-one (31) selected quoted manufacturing companies in Nigeria for a period of 16 years that were split into eight (8) years of historical cost accounting method (2004-2011) and eight (8) years of fair value measurement valuation technique method (2012-2019). The study utilized the paired sample t-test framework in analyzing the data. Findings revealed that there are significant differences between the impact of historical cost accounting and fair value measurement valuation technique on firm performance. Thus, the study recommended among others that the Financial Reporting Council of Nigeria should focus on the compliance level of companies with fair value accounting in addition to taking necessary steps to improving the understandability and usage of fair value accounting.